Can green city branding support China's Sponge City Programme?. Issue 1 (13th June 2022) - Mitchell, Gordon; Chan, Faith Ka Shun; Chen, Wendy Y.; Thadani, Dimple R.; Robinson, Guy M.; Wang, Zilin; Li, Lei; Li, Xiang; Mullins, May-Tan; Chau, Patrick Y. K.
Abstract: China's Sponge City Programme (SCP) is one of the world's most ambitious sustainable urban drainage programmes. By 2030, Chinese cities must have 80% of their land drained by Blue–Green Infrastructure (BGI) to build critically needed flood resilience. Costs must be met from municipal and private finance, but BGI lacks the revenue streams of public assets like utilities, so has limited appeal to public–private partnerships. Finance options, including Green Bonds targeting institutional investors, and Payment for Urban Ecosystem Service schemes targeting local citizens and businesses, need developing. Green city branding could lever such finance but despite widespread use of green branding to attract investment, sponge branding strategies are immature, and alignment is needed in green branding between sponge project type (e.g., flagship and retrofit), financial instrument, and target financier, to develop differentiated brands that appeal to a diversity of SCP investors. With little grassroots input into city branding, and SCP problems of green gentrification, local support for SCP implementation may be at risk. This is concerning, because cities need local citizens and businesses to invest in the SCP to achieve the extensive retrofit needed, as retrofit (using small-scale BGI such as stormwater planters, de-paving, and raingardens) has little appeal for institutional investors. HIGHLIGHTS: The SCP is critical to climate adaptation of Chinese cities. Major investment is needed to deliver the necessary BGI. Green city branding exploiting Sponge City BGI in 30 cities is reviewed. To secure finance, city branding and financial instruments must be better aligned. Graphical Abstract